Exponential stability of integral time-varying delay system. Issue 12 (2nd December 2022) - Gao, Xiangyu; Teo, Kok Lay; Yang, Hongfu; Cong, Shen
Abstract : This paper investigates exponential stability problem of integral time-varying delay system. Based on a novel exponential stability theorem, sufficient conditions for exponential stability of integral time-varying delay system are obtained in the form of coupled linear matrix inequalities (LMIs). These sufficient stability conditions cover some previous results as special cases when the integral time-varying delay system reduce to the integral time-invariant delay system. These sufficient conditions cannot be obtained directly from Theorem 1 given in Li, Zheng, and Wang [(2016). Exponential stability analysis of integral delay systems with multiple exponential kernels. Journal of the Frankline Institute, 353, 1639–1653. https://doi.org/10.1016/j.jfranklin.2015.12.016 ] due to the presence of time-varying delays. This is the main motivation for the research being carried out in this paper. Four example s are provided to show the effectiveness and advantages of the proposed method.